1005 Calculated Inhaled Albuterol Dose and Delivered Albuterol Dose During Simulated Infant Ventilation Using a Novel Ventilator Circuit Connector. (October 2012) - Mazela, J; Chmura, K; Kulza, M; Florek, E; Gregory, TJ; Henderson, C; Keszler, M
Abstract : Background: Dose determination of aerosolized medications administered to ventilated infants is based on nominal dose and not on the calculated target inhaled dose. A novel ventilator circuit connector (VCC) (AFECTAIR ®, Discovery Laboratories, Inc. Warrington, PA), has been developed to facilitate inhaled therapies to ventilated patients. Objective: The aim of the study was to evaluate the difference between the calculated inhaled dose (ID) and the actual delivered dose (DD) in an in vitro simulated infant ventilation system using the VCC vs standard of care (SoC). Design/methods: Albuterol sulfate (AS) was aerosolized with a jet nebulizer and delivered using SoC and VCC. Aerosolized AS was collected on HME filters placed before a test lung under different ventilation conditions. DD was determined by rinsing the filters and using an HPLC assay for AS. The calculated ID was determined using the formula: ID=Ca*Vm, (Ca=aerosol concentration, Vm=m inute ventilation). Results: There was a 10–14 fold increase in the in vitro DD of AS at various ventilation conditions when using the VCC compared with SoC. The difference between the calculated ID and the measured DD in vitro ranged from –42% to 15% for the VCC and from –388% to –158% for SoC. Conclusions: The VCC delivered a higher AS dose in vitro that was more representative of the calculated ID compared with SoC. The VCC may allow for a more accurate approximation of actual DD of inhaled therapies when targeting a calculated ID for critical care patients. Supported by PUMS and Discovery Laboratories, Inc.